PERILAKU PENCARIAN INFORMASI SISWA DALAM MODEL PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - Mindy Syailah Nurthoyyibah; Susanti Agustina (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
The pandemic Covid-19 has impact most of human activities, one of them is education. The implementation of distance learning has influence for the parents, teachers, and students who are the main subjects in education, as though increased stress, less of competency development, or technical learning problems related to fulfill information needs. In case the problems abandoned, it will hinder the students-development, the development of sustainable education, and the progress of the nation. This research aims to determine the information behavior of students of SMAN 1 Cicalengka in overcome learning constraints during the pandemic Covid-19. This research uses a qualitative approach with descriptive methods. Data collection techniques is using triangulation data, through observation/surveys, interviews, and literature study. The population were all students of SMAN 1 Cicalengka with 5 informants. It uses the Ohotshi-Gottschalg-Duque information-behavior model as conceptual framework. The results showed that: First, students information needs were at the concious, visceral, and adapted levels; Second, information needs are mostly related with learning materials, motivation, health, hobbies, college even job vacancies; Third, students information behavior based on habits and intuitions, most of students do not understand the process of extracting because they do not recognize the domain of the information need. The implication that learning based on library is necessity at the level of educational unit that collaborates between teachers and school librarians.